Miskonsepsi Siswa Kelas IV Sekolah Dasar Materi Bangun Datar Berbasis Three-Tier Test - Vinda Kusuma, Rachmalia; Mizan , Saeful; Wayuningati , Nita Retno (Papanda, 2025)
Misconceptions can have a significant negative impact on students' learning processes. Students who hold misconceptions may struggle to solve problems related to the concept, and they may also face difficulties in understanding subsequent concepts that are connected to it. This study aims to identify the misconceptions of fourth-grade students at SDN Bareng 1 Kota Malang on the topic of plane figures using the Three-Tier Test. The research method employed is descriptive qualitative with 21 students as research subjects. The sampling technique used in this study is purposive sampling, selecting 21 students from class 4B at SDN Bareng 1 Kota Malang as the research subjects because they had studied the topic of plane figures during the even semester. The data collection technique used is the Three-Tier Test. The data analysis techniques applied in this study include data reduction, data presentation, and conclusion drawing. The results of the study show that students experienced misconceptions at a rate of 68.57%. These misconceptions include false positive misconceptions, false negative misconceptions, and pure misconceptions. The causes of the students’ misconceptions were identified as factors related to teachers, learning media, and student reception.